Effects of income inequality and governance on energy poverty alleviation: Implications for sustainable development policy. (October 2022) - Acheampong, Alex O.; Shahbaz, Muhammad; Dzator, Janet; Jiao, Zhilun
Abstract: This paper examines the effects of income inequality and governance on access to electricity using a panel of 43 SSA countries from 1990 to 2017. The results from the two-step GMM estimator revealed that while income inequality substantially reduced access to electricity, governance has been ineffective in improving it. The findings showed that governance interacts with income inequality and economic growth to reduce access to electricity. Comparative analysis suggested that these findings vary among the SSA sub-regions. We argue that energy poverty alleviation requires firm political will and an effective governance system to close the income inequality gap. Highlights: Examines the effect of income inequality and governance on energy-poverty alleviation. Income inequality substantially reduced access to electricity. Governance has been ineffective in enhancing access to electricity. Governance indirectly reduces access to electricity through income inequality and GDP. Effective governance systems and distributional policies are needed to alleviate energy poverty.